Beyond the Classroom: Online Learning, Legal Awareness, and Strategic Communication for Early Marriage Prevention in Remote Indonesian Communities - Ade Nur Istiani; Erina Pane (Online Learning In Educational Research (OLER), 2026)
Early marriage remains a persistent challenge in remote Indonesian communities, where cultural traditions, economic vulnerability, and limited legal awareness continue to influence adolescents’ marriage decisions. This sequential explanatory mixed-methods study investigated how online learning, legal awareness initiatives, formal education, and strategic communication collectively contribute to legal awareness, attitudes, and early marriage intention across geographically diverse Indonesian communities. Quantitative survey data from adolescents were complemented by interviews and focus group discussions to provide a contextual understanding of the observed patterns. The findings revealed substantial disparities in legal awareness across community settings and showed that parental attitudes, educational attainment, and engagement with online learning were consistently associated with adolescents’ intentions regarding early marriage. Qualitative evidence further highlighted that peer advocacy, community leadership, and digitally supported learning created socially acceptable spaces for discussing sensitive legal and social issues, although their long-term effectiveness requires further evaluation. Overall, the study suggests that integrating online learning with legal education and community-based strategic communication offers a promising approach to strengthening legal awareness and supporting early marriage prevention in underserved communities. Given the cross-sectional design, the findings should be interpreted as evidence of improved awareness, attitudes, and engagement rather than confirmed behavioral change. These results provide practical guidance for designing culturally responsive and context-sensitive digital education programs in remote settings.